Green Employee Empowerment/Engagement/ and Non-Financial Corporate Performance in Deposit Money Banks of South-West, Nigeria - Olatuni Eniola Sule; Edwinah Amah; Drusilia Adekemi Alagah (Newinera Publisher, 2021)
The study examined the relationship between green employee empowerment/engagement and non-financial corporate performance in deposit money banks of South-West, Nigeria. Survey design was used. The study population was the managerial staff of deposit money banks in the South-West of Nigeria with 330 as the sample size. Simple random sampling technique was applied. Structural Equation Modelling - AMOS was used in testing the three (3) hypotheses. The findings revealed that there is a relationship between green employee empowerment/engagement and non-financial corporate performance with the estimate (ꞵ) between .136 and .969 in all the three (3) hypotheses and that green empowerment/engagement positively aid the non-financial performance in deposit money banks in South-West, Nigeria. Hence, the study recommended that green employee empowerment/engagement should be embraced to improve non-financial performance like employee satisfaction, operational efficiency, and innovation.